Forage characteristics and beef cattle production in perennial pastures of BRS Paiaguás and BRS Piatã in integrated crop livestock system - Sekiya, Bianca Midori Souza [UNESP]; Lupatini, Gelci Carlos [UNESP]; Andrighetto, Cristiana [UNESP]; De Oliveira Neves, Franciely [UNESP]; Marangoni, Guilherme Antônio Oliveira [UNESP]; Mulero, Jeferson [UNESP]; Lopes, Rodrigo Medina (Universidade Estadual de Londrina, 2021)
The integrated crop-livestock system is highlighted in Brazilian agriculture, in which the synergism between the components can increase productivity and animal performance. Forage is one of the most important components because it is the basis of animal feed. Thus, the objective of the study was to evaluate the beef cattle production and pastures characteristics of Urochloa brizantha BRS Piatã and BRS Paiaguás , under continuous grazing in an integrated crop livestock system. The experiment was conducted in west of Sao Paulo State, in a randomized complete block design with two treatments and three replicates, from October 2018 to June 2019. The treatments were 3-year-old pastures of BRS Piatã and Paiaguás, in an integrated crop livestock system with perennial pasture and soybean. Nellore steers (14 ± 2 months old and 244 ± 13 kg initial weight) were used. The grazing method adopted was a continuous stocking with a variable rate to maintain a pasture height of 30 cm. Herbage mass was 5716 and 5480 kg dry matter ha-1 for Piatã and Paiaguás, respectively. The crude protein, neutral detergent fiber, and acid detergent fiber were similar between the two cultivars. The leaf blade mass of BRS Piatã was greater than that of BRS Paiaguás in summer. Animal performance was similar between treatments, with average daily gain of 0.901 and 0.822 kg day-1 and weight gain per area of 888 and 865 kg ha-1 in Piatã and Paiaguás, respectively. The BRS Piatã and BRS Paiaguás grasses are indicated for use in perennial pastures in integrated crop livestock systems.
Keywords: Animal performance; Cultivars; Morphological composition; Urochloa brizantha.